Integration of Artificial Intelligence Marketing to Get Brand Recognition for Social Business - Shaily, Sharjana Alam; Emma, Nazmun Nahar (International Review of Management and Marketing, 2021)
The purpose of this article is to conduct a detailed analysis of the integration of Artificial Intelligence (AI) marketing to get brand recognition for social business. It has been seen that AI is immensely popular with businesses these days. This article mainly focuses on the use of AI marketing elements to increase brand recognition for social businesses, which are not very well-known to consumers in Bangladesh. This study makes use of a quantitative research approach that includes a survey questionnaire used to explain the kind of impact AI may have on brand recognition for social businesses. The authors have approached 500 respondents and got close to an 81% response rate, 403 responses. With the support of SPSS, the collected answers from the sample were analyzed. The results show that integration of AI marketing strategies will play a significant role in leading to increase brand awareness and recognition for social business. This research will allow the professionals to integrate AI marketing elements to achieve improved brand recognition. This study will also encourage establishing of more social businesses ultimately benefiting society. Keywords: Artificial Intelligence Marketing, Brand Awareness, Brand Recognition, Social Business, Social Businesses in Bangladesh. JEL Classifications: M31, L31 DOI: https://doi.org/10.32479/irmm.11542